Timeline of Curriculum Policy in Indonesia - Hikmawati, Nisrina; Hosnan, Hosnan (Institut Agama Islam Negeri Lhokseumawe, 2022)
Purpose of the study: To form the curriculum policy timeline in Indonesia that is essential in understanding and analyzing education development in Indonesia. Methodology: This study uses the library research method, taking from various sources, textbooks, and other scientific papers. Main Findings: The Indonesian curriculum policy has undergone 13 changes, summarized in 4 periods, namely 1) the independence period and the old order, 2) the new order period, 3) the reform period, and 4) the covid-19 pandemic period. Novelty/Originality of this study: So that interested parties in education can have a foothold to develop, evaluate and forecast the curriculum. In addition, Education implementers can have an open paradigm in developing curricula so that the curriculum does have to change. As the faster human civilization develops, the educational curriculum will often change.